Bio-based aliphatic/aromatic poly(trimethylene furanoate/sebacate) random copolymers: Correlation between mechanical, gas barrier performances and compostability and copolymer composition. (January 2022) - Zubkiewicz, Agata; Szymczyk, Anna; Sablong, Rafaël J.; Soccio, Michelina; Guidotti, Giulia; Siracusa, Valentina; Lotti, Nadia
Highlights: Novel high molecular weight 100% bio-based random aliphatic-aromatic copolymers of PTF containing different amounts of sebacic acid were synthesized by eco-friendly polycondensation in the melt. Low amounts of PTSeb comonomeric units significantly modify PTF thermal, mechanical and barrier properties and render the final material compostable. PTF15PTSeb copolyester exhibited superior gas barrier properties to O2 and CO2, and temperature induced shape memory behavior, which foreshadows possible new applications, including as example biomedical ones, for these new PTF copolymers beyond food packaging ones. Abstract: Highly promising fully biobased random copolyesters, poly(trimethylene 2, 5-furandicarboxylate- co -trimethylene sebacate) (PTFcoPTSeb), were synthesized by using bio derived 1, 3-propanediol, dimethyl ester of 2, 5- furandicarboxylic acid, and sebacic acid, through eco-friendly polycondensation in the melt. Copolymers with high molecular weight containing 5, 15, 25 mol % of PTSeb were obtained, and their chemical structure confirmed by 1 H NMR and FTIR spectroscopy. The thermal, tensile and gas barrier properties and composability were studied in relation to the copolymer supramolecular structure. As expected, introduction of PTSeb co-units results in lowering of glass transition temperature of copolymers and improves their flexibility. Besides, all copolymers showed outstanding gas barrier properties to O2 and CO2, with copolymer containing 15 mol % of PTSeb showing exceptional gas barrier properties, better than those of PTF and comparable to those of EVOH, currently used in multilayer packaging films. The same copolymer exhibited temperature induced shape memory behaviour. It was found that low amounts (15-25 mol %) of PTSeb in copolymer significantly modifies PTF thermal, mechanical and barrier properties and renders the final material compostable. Copolyesters containing 15 and 25 mol % of PTSeb can compete in some applications with commercially available compostable Ecoflex® polymer, but with markedly improved barrier properties.